Bilateral Retinal Vasculopathy Associated with Autosomal Dominant Dyskeratosis Congenita. Issue 5 (September 2013) - Vaz-Pereira, Sara; Pacheco, Patricio A.; Gandhi, Shreyans; Kulasekararaj, Austin G.; Marsh, Judith C.; Pal, Bishwanath; Mufti, Ghulam J.
Purpose: To report a case of autosomal dominant dyskeratosis congenita (AD-DC) complicated by bilateral retinal vasculopathy and proliferative retinopathy with vitreous hemorrhage in the right eye, in the absence of pancytopenia . Methods: We report a 32-year-old woman who presented with floaters in her right eye. She underwent complete ophthalmic examination and fundus fluorescein angiography . Results: Funduscopic examination revealed vascular sheathing in the temporal periphery of both eyes and a vitreous hemorrhage in the right eye. Fluorescein angiography showed retinal neovascularization in the right eye and bilateral temporal peripheral capillary nonperfusion. Treatment consisted of laser photocoagulation directed to the areas of capillary nonperfusion in both eyes. A point mutation in the TERC gene confirmed the diagnosis of AD-DC . Conclusions: Autosomal dominant dyskeratosis congenita is a rare form of inherited bone marrow failure and its presentation is milder than seen in patients with X-linked and autosomal recessive mutations. These patients may lack the classic clinical triad, so it is important to have a high index of suspicion and to be aware of retinal vasculopathy as a complication of dyskeratosis congenita as it may severely compromise vision. Appropriate treatment includes prompt laser photocoagulation to areas of retinal nonperfusion .